'And makes it indistinct / As water is in water': The melting away of the heroic subject in Antony and Cleopatra and All for Love. Issue 1 (November 2020) - Velissariou, Aspasia
Premising the structural importance of water imagery in William Shakespeare's Antony and Cleopatra, Antony's 'liquefaction' reflects the core of his interiority, which is identified with his love affair with Cleopatra. Their desire requires a third party, Rome, in relation to which a seemingly self-enclosing erotic universe is built, and against which Antony fights for ascendancy, as a ghostly heroic self. In John Dryden's All for Love, the historical flux vanishes, Antony's heroic past figures as a residue and history as an embarrassment to love. In contrast with Shakespeare's heroes, the lovers' domestication foregrounds the compatibility of love and eros within marriage.